Arte ai margini - QUATTROCCHI, Luca (Firenze University Press, 2025)
The catalogue of the exhibition Art on the Margins reconstructs the history of the painting atelier of the former neuropsychiatric hospital of Arezzo, once located in the Pionta complex, where the Arezzo Campus of the University of Siena is today located. The atelier was founded in 1958 by Dr. Furio Martini, psychiatrist and deputy director of the hospital, who initially availed himself of the collaboration of the Roman painter Franco Villoresi. In the exhibition there are around eighty works created by patients, many of which are preserved in the archives of the University of Siena. After Bianca Tosatti’s introduction, the catalogue opens with a contribution by Roberto Boccalon on the connections between art and psychiatry. Luca Quattrocchi’s essay analyzes Franco Villoresi’s activity, before and during the years in which he was ‘master’ in the hospital atelier. The artistic laboratory is then presented with a selection of pictorial works by some patients, edited by Sabrina Picchiami, up to the main section of the exhibition: the activity of Livio Poggesi, the most assiduous and able student-patient of the atelier, by Paolo Torriti. The volume ends with a contribution on the archives of psychiatric hospitals and particularly on the Arezzo one, written by Stefano Moscadelli, Antonella Moriani and Lucilla Gigli.